A Dynamic Panel Analysis of Drivers of Output Growth in the Nigerian Manufacturing Firms - Olawumi, Ojo Rufus; Ogungbenle, Sola (European Scientific Journal, ESJ, 2018)
Regardless of the efforts of government to revamp the manufacturing sector in Nigeria, the sub-sector has remained ineffective with dwindling output and there have been consistent fluctuations in the share of the manufacturing sub-sector to Gross Domestic Product (GDP) in Nigeria. This study therefore examines the determinants of output growth in the Nigerian formal manufacturing sub-sector. The study made use of fifty (50) formal manufacturing firms listed in the Nigerian Stock Exchange Data for the formal manufacturing firms were sourced from the Nigeria Stock Exchange (NSE) Fact Book and the Central Bank of Nigeria Statistical Bulletin 2014. The estimated models in the study were specified following the works of Sangosanya (2011). The study employed the dynamic panel data analysis (the dynamic models of the Generalized Method of Moments (GMM) and the Systemic Generalized Method of Moments (SYSGMM)) for the Nigerian formal manufacturing sub-sector. The study showed that the coefficient of operating efficiency in the GMM&SYSGMM estimate, i.e. -0.0349214 and -0.0199787 respectively showed a negative relationship between OPREF and firms’ growth. This implied that information supplied by firms about their growth indicators is at variance with their performance. This further speaks volume of the weakness of regulatory agencies to effectively monitor the performance of manufacturing firms in Nigeria. Also, the study showed that exchange rate, bank efficiency and managerial efficiency have significant positive relationship with output growth of firms. Also variables such as degree of financial development, energy infrastructural facilities and government regulations and policy have significant negative impact with output growth of firms in Nigeria. Findings revealed that all the explanatory variables identified in the study are strong determinants of firm growth in the Nigerian manufacturing sub-sector. The study recommended among others that government should formulate and implement policies that would hinder formal manufacturing firms from publishing fake report of their growth. Also, government should formulate and implement policy measures that would make imported goods more expensive and appropriate monetary policies that would make the cost of borrowing from banks (interest rate) affordable should be priotised in Nigeria.